PENANAMAN NILAI-NILAI MULTIKULTURAL MELALUI PENDIDIKAN AGAMA ISLAM DI MA NURUL AKHLAQ BIARO BARU KABUPATEN MUSI RAWAS UTARA - ENDANG ARDIANSAH (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2021)
The problems raised in this study are what are the forms of multicultural Islamic education values and how the implementation and results of the cultivation of multicultural values through Islamic religious education at MA Nurul Akhlaq Biaro Baru, Karang Dapo District, Musi Rawas Regency. To answer the above problems, the writer uses descriptive qualitative research. From the research results it was found that 1) the values of multicultural Islamic education at Madrasah Aliyah Nurul Akhlaq Biaro Baru, Karang Dapo District, Musi Rawas Utara Regency, namely the value of tolerance, the value of equality / equality, the value of unity, the value of kinship / brotherhood and the value of justice. 2) The implementation of the cultivation of multicultural values through Islamic religious education at MA Nurul Akhlaq Biaro Baru, Karang Dapo District, Musi Rawas Regency is carried out in 2 ways, first in the classroom through Islamic Religious Education using an active and communicative teaching model with discussion and questioning methods. answer. Second, outside the class, namely Rohis activities, Mabit (night of faith and piety building) and student council activities. 3) The results of planting multicultural values through Islamic religious education at MA Nurul Akhlaq Biaro Baru, Karang Dapo District, Musi Rawas Regency can be seen from the habits of students in responding to multicultural values such as the value of teloransi, democratic values, the value of equality / equality as well as the value of justice in everyday life both inside and outside the classroom